2017
DOI: 10.3389/fnbeh.2017.00049
|View full text |Cite
|
Sign up to set email alerts
|

Lack of β2-AR Increases Anxiety-Like Behaviors and Rewarding Properties of Cocaine

Abstract: It is well known that β-adrenoceptors (β-ARs) play a critical role in emotional arousal and stressful events, but the specific contributions of the β2-AR subtype to the psychological disorders are largely unknown. To investigate whether β2-AR are involved in anxiety-like behavior and reward to addictive drugs, we conducted a series of behavioral tests on β2-AR knock-out (KO) mice. β2-AR KO mice exhibited increased preference for the dark compartment and closed arm in tests of Light/Dark box and elevated plus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Clinical and preclinical studies have already reported the anxiolytic effect of CVD, strengthening the data presented here [63,64,66,67]. However, studies addressing neuroinflammatory mechanisms underlying the action of this drug are still scarce, mainly using stress models of anxiety.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Clinical and preclinical studies have already reported the anxiolytic effect of CVD, strengthening the data presented here [63,64,66,67]. However, studies addressing neuroinflammatory mechanisms underlying the action of this drug are still scarce, mainly using stress models of anxiety.…”
Section: Discussionsupporting
confidence: 77%
“…One of the mechanisms related to this dysregulation is the activation of betaadrenergic receptors in glial cells and some brain regions. Thus, the blockade of these receptors seems to be an important anxiolytic strategy already observed in animal models and human studies [63][64][65][66][67]. Indeed, we observed that CVD was superior to DVS in regulating anxiety-like alterations induced by CUS, probably due to its nonselective blockade of adrenergic receptors.…”
Section: Discussionmentioning
confidence: 51%
“…β-ARs activation enhances glutamatergic transmission in CeL, via increasing presynaptic co-release of NE and glutamate ( Silberman and Winder, 2013 ), and our results showed that rVNS increased the frequency of mEPSCs in CeL, suggesting that rVNS might elevate NE levels that led to an increased neuronal activation in CeL. Importantly, the activation of β-ARs by NE is thought to mediate memory process, defensive behavior, and anxiety-like behavior ( Liang et al, 1986 ; Watanabe et al, 2003 ; Zhu et al, 2017 ). There are several findings indicate that activation of the noradrenergic system decreases anxiety-like behavior and promotes an active coping strategy in response to stressors ( Chen et al, 2019 , Khoshbouei et al, 2002 ), which is crucial for the behavioral effects of rVNS.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, the results showed that, unlike other psychological characteristics, only anxiety attacks showed a better association with ECG (Section 4.2). It is possible that anxiety attacks are associated with distinct β-adrenergic dysregulation ( 73 , 74 ) and psychophysiological mechanisms, compared to those seen with trait anxiety (STAI), trait depression (BDI), and self-reported episodes of depression. This could be a relevant theme for future research.…”
Section: Discussionmentioning
confidence: 99%